An Active In-Home Physician Model of Palliative Care and Its Resulting Performance Indicators Related to Home Deaths, Unplanned Emergency Department Visits and Unplanned Hospital Admissions. Issue 1 (January 2021) - Webber, Colleen; Valiulis, Aurelia Ona; Tanuseputro, Peter; Schulz, Valerie; Apramian, Tavis; Schreier, Gil; Hamilton, Kirk
Background: Limited research has characterized team-based models of home palliative care and the outcomes of patients supported by these care teams. Case presentation: A retrospective case series describing care and outcomes of patients managed by the London Home Palliative Care Team between May 1, 2017 and April 1, 2019. Case management: The London Home Palliative Care (LHPC) Team care model is based upon 3 pillars: 1) physician visit availability 2) active patient-centered care with strong physician in-home presence and 3) optimal administrative organization. Case outcomes: In the 18 month study period, 354 patients received care from the London Home Palliative Care Team. Most significantly, 88.4% ( n = 313) died in the community or at a designated palliative care unit after prearranged direct transfer; no comparable provincial data is available. 21.2% ( n = 75) patients visited an emergency department and 24.6% ( n = 87) were admitted to hospital at least once in their final 30 days of life. 280 (79.1%) died in the community. These values are better than comparable provincial estimates of 62.7%, 61.7%, and 24.0%, respectively. Conclusion: The London Home Palliative Care (LHPC) Team model appears to favorably impact community death rate, ER visits and unplanned hospital admissions, as compared to accepted provincial data. Studies to determine if this model is reproducible could support palliative care teams achieving similar results.